Cum Grano Salis: Cardiac Sarcoidosis as a Perfect Mimic of Arrhythmogenic Right Ventricular Cardiomyopathy. (30th June 2021) - Saturi, Giulia; Caponetti, Angelo Giuseppe; Leone, Ornella; Lovato, Luigi; Longhi, Simone; Graziosi, Maddalena; Ditaranto, Raffaello; Biffi, Mauro; Galiè, Nazzareno; Biagini, Elena
Abstract : Supplemental Digital Content is available in the text.